German guidelines on screening, diagnosis, and treatment of alcohol use disorders: update 2021 : guidelines - Kiefer, Falk; Batra, Anil; Petersen, Kay Uwe; Ardern, Isabel Sophie; Tananska, Daniela; Bischof, Gallus; Funke, Wilma; Lindenmeyer, Johannes; Mueller, Sebastian; Preuss, Ulrich W.; Schäfer, Martin; Thomasius, Rainer; et al. (European addiction research, 2022)
Introduction: Alcohol consumption in Germany is associated with considerable health and economic consequences. In addition to prevention, the early detection and differential treatment of those affected play an important role. The guideline “Screening, Diagnosis, and Treatment of Alcohol Use Disorders” forms the basis of this care for people suffering from alcohol use disorders. Regular updates integrate the current state of research evidence and clinical expertise. Methods: Under the auspices of the German Society for Psychiatry, Psychotherapy, Psychosomatics, and Neurology and the German Society for Addiction Research and Addiction Therapy e.V. (DG-Sucht), the 2019-2020 S3 guideline on alcohol was revised by eight working groups. Thirty-five professional societies participated in a structured consensus process to deliberate the recommendations. Potential conflicts of interest were examined in advance, documented, and taken into account during the voting on the recommendations. Results: The guideline provides recommendations on screening and brief interventions for different groups of people, as well as on treatment of individuals in the acute and post-acute phases of withdrawal. Special emphasis was placed on the treatment of comorbid somatic and psychological disorders. In addition, recommendations for specific groups of people (e.g., children and adolescents, pregnant women) have been made and adapted to the German care landscape.